2013
DOI: 10.1186/1756-0500-6-225
|View full text |Cite
|
Sign up to set email alerts
|

The influence of applying insurance medicine guidelines for depression on disability assessments

Abstract: BackgroundIn the current study we report on the effects of an implementation strategy in the form of a training programme on the assessed work limitations of a client with depression by insurance physicians (IPs) participating in a RCT. These assessed work limitations of a client were in the form of scores on the List of Functional Abilities (LFA).MethodWe conducted a randomised controlled trial (RCT) for IPs in which we compared the intervention of a specially developed training programme with the usual metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Of 4562 potentially relevant citations identified, 101 reports proved potentially eligible after we had screened titles and abstracts. On full text screening, 23 studies, 9 11 22 23 24 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 including four non-English studies, 9 39 40 41 proved eligible for analysis (fig 1 ). All studies were published from 1992 onwards and enrolled disability claimants from 12 countries in Europe, North America, Australia, the Middle East, and northeast Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 4562 potentially relevant citations identified, 101 reports proved potentially eligible after we had screened titles and abstracts. On full text screening, 23 studies, 9 11 22 23 24 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 including four non-English studies, 9 39 40 41 proved eligible for analysis (fig 1 ). All studies were published from 1992 onwards and enrolled disability claimants from 12 countries in Europe, North America, Australia, the Middle East, and northeast Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In the insurance setting, 13 studies including 463 patients and 367 raters explored agreement between medical experts (two or more experts assessing the same patient) (table 1 ; appendix 4). 9 11 22 23 24 32 34 37 39 43 44 45 46 Three studies including 3729 patients (with 3562 patients from a single centre 33 ) and eight raters (information was lacking from one study 33 ) explored agreement between medical experts and claimant’s treating physicians 33 or independent rehabilitation or occupational health teams with a mandate to care. 38 42 The median number of patients per study was 13.5 (range 1-3562), and the median number of raters per study was 12 (2-103, excluding one study that did not report the number of raters 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…The provision of recent and relevant evidence can support OHPs in their guidance or assessment tasks. Several guidelines have been developed, incorporating recent evidence, with the aim of improving the quality of guidance or assessment given by OHPs [ 4 , 5 ]. One of these guidelines is the ‘Work participation of people with a chronic disease’ guideline [ 6 ], which aims to support the work participation of people with a chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of knowledge and skills provided by a guideline [ 6 ] can lead to a higher quality of occupational care [ 4 , 5 ], guideline adherence by OHPs is generally low [ 7 9 ]. Previous studies have shown that guideline use is influenced by various factors that may act as barriers, which are related to the professional, the individual with a chronic disease, or to the knowledge included in the guideline [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intra-class correlation coefficient (ICC) should be at least 0.6 to be useful [ 42 ], which seems achievable in the insurance medicine context. [ 43 , 44 ] With a sample size of 30 claimants, each evaluated by four raters, we expect to estimate an assumed ICC of at least 0.6 with a precision expressed as the width of a two sided 95 % confidence interval (CI) of ± 0.15 [ 45 ].…”
Section: Methodsmentioning
confidence: 99%